Optimization Of Student Management As A Pillar Of Educational Institutions In Indonesia - Sari, Tanti Nurmala; Jumrodah; Supriatin, Atin (Jurnal Manajemen Pendidikan, 2025)
Background Student management plays a very crucial role in supporting the success of educational institutions in Indonesia. Effective management will create a conducive learning environment, strengthen character formation, and support the development of students' overall potential. Purpose The purpose of this study is to analyze educational conflict in Islamic boarding schools. The research methodology used is a literature review. Design/method/approach The research methodology used is a literature review. Results The research results show that student management that is structured and based on good management principles, such as planning, organizing and evaluating can strengthen the capacity of educational institutions to achieve their goals. In the context of Indonesian education, the role of student management is becoming increasingly important in line with social, cultural changes and the increasingly complex needs of the world of work. This article aims to examine how student management can support the quality of educational institutions, especially in improving the quality of the learning process and student welfare. Contribution/value This article also highlights the importance of collaboration between schools, parents and the community in carrying out effective student management, in order to create quality education that is relevant to the needs of the times.